How innovations in methodology offer new prospects for volume electron microscopy. (27th July 2022) - Kievits, Arent J.; Lane, Ryan; Carroll, Elizabeth C.; Hoogenboom, Jacob P.
Abstract: Detailed knowledge of biological structure has been key in understanding biology at several levels of organisation, from organs to cells and proteins. Volume electron microscopy (volume EM) provides high resolution 3D structural information about tissues on the nanometre scale. However, the throughput rate of conventional electron microscopes has limited the volume size and number of samples that can be imaged. Recent improvements in methodology are currently driving a revolution in volume EM, making possible the structural imaging of whole organs and small organisms. In turn, these recent developments in image acquisition have created or stressed bottlenecks in other parts of the pipeline, like sample preparation, image analysis and data management. While the progress in image analysis is stunning due to the advent of automatic segmentation and server‐based annotation tools, several challenges remain. Here we discuss recent trends in volume EM, emerging methods for increasing throughput and implications for sample preparation, image analysis and data management. Lay description: A key concept in biology is that the structure of tissues, cells and their components (cell organelles) often relates to their function. With electron microscopy (EM), it is possible to reveal this structure with nanometre resolution and therefore infer about its function. Electron microscopy of tissues knows a long history of method development, starting in the 1940s. Method development has largely determined the possibilities and scope of electron microscopy. In the 2000s, innovative techniques were developed that allowed routine imaging of tissues in 3D with a higher degree of automation. Nevertheless, conventional electron microscopy techniques remain unsuited for imaging of tissue with nanometre resolution on a millimetre scale because of their low inherent throughput. Here we analyse trends in volume electron microscopy (EM of tissues in 3D) by reviewing the application, acquisition parameters and data information from over 100 publications in the field. We see an expansion of interest from the conventional applications in neuroscience to other fields, such as cell biology. Additionally, the size of data sets is growing rapidly. From here, we review in detail how certain developments in methodology from the past 10 years have tried to overcome the low acquisition throughput of electron microscopes, by making these techniques more robust during long acquisitions, but also much faster by parallelisation. We find that these new developments have big implications for sample preparation, processing and analysis of the images and data management. We therefore also describe the new developments in these separate domains. We illustrate how novel sample preparation protocols have been developed specifically for larger volumes, how the introduction of machine learning has accelerated automated segmentation of volume EM data and that there is an ongoing transition from local to remote data storage and management. We also touch upon the tools that researchers use to analyse and annotate EM data. We conclude that the potential of volume EM remains high and the new developments open up possibilities for novel biological studies. We promote the sharing of resources and tools between researchers and institutions to maximise the potential from the new developments in volume electron microscopy.